Effective community energy management through transactive energy marketplace. (July 2021) - Bokkisam, Hanumantha Rao; M.P., Selvan
Abstract: This paper presents a framework of transactive energy marketplace for effective community energy management with demand response and peer-to-peer energy trading. Further, this paper focuses on improving the monetary benefits to the participants by trading their excess generation/demand with the neighborhoods in addition to the upstream utility. Participants trade their net energy at cost-effective internal market prices determined by a transactive energy market operator. The supply-to-demand ratio based market pricing mechanism is employed to determine the day-ahead internal market prices. A case study is conducted using the data collected from ten participants in a residential community of Trichy, India. The case study results validate the effectiveness of the proposed framework in improving the monetary benefits of the market participants and reducing the grid dependency. The reduction in community electricity bill is found to be between 28% and 68% in different scenarios with the proposed market compared to the traditional market. Graphical abstract: Highlights: Development of a transactive energy marketplace (TEM) framework. Development of a transactive home energy management system (THEMS). Development of a collaborative consumption-based demand response algorithm .